Systemic Inflammation after Uniport, Multiport, or Hybrid VATS Lobectomy for Lung Cancer - Tacconi, Federico; Carlea, Federica; La Rocca, Eleonora; Vanni, Gianluca; Ambrogi, Vincenzo (The Thoracic and Cardiovascular Surgeon, 2021)
Background Different video-assisted thoracic surgery (VATS) approaches can be adopted to perform lobectomy for non-small cell lung cancer. Given the hypothetical link existing between postoperative inflammation and long-term outcomes, we compared the dynamics of systemic inflammation markers after VATS lobectomy performed with uniportal access (UNIVATS), multiportal access (MVATS), or hybrid approach (minimally invasive hybrid open surgery, MIHOS).Methods Peripheral blood-derived inflammation markers (neutrophil-to-lymphocyte [NTL] ratio, platelet-to-lymphocyte [PTL] ratio, and systemic immune-inflammation index [SII]) were measured preoperatively and until postoperative day 5 in 109 patients undergoing UNIVATS, MVATS, or MIHOS lobectomy. Differences were compared through repeated-measure analysis of variance, before and after 1:1:1 propensity score matching. Time-to-event analysis was also done by measuring time to NTL normalization, based on the reliability change index for each patient.Results After UNIVATS, there was a faster decrease in NTL ratio (p = 0.015) and SII (p = 0.019) compared with other approaches. MVATS exhibited more pronounced PTL rebound (p = 0.011). However, all these differences disappeared in matched analysis. After MIHOS, NTL ratio normalization took longer (mean difference: 0.7 ± 0.2 days, p = 0.047), yet MIHOS was not independently associated with slower normalization at Cox's regression analysis (p = 0.255, odds ratio: 1.6, confidence interval: 0.7–4.0). Furthermore, surgical access was not associated with cumulative postoperative morbidity, nor was it with incidence of postoperative pneumonia.Conclusion In this study, different VATS approaches resulted into unsubstantial differences in postoperative systemic inflammatory response, after adjusting for confounders. The majority of patients returned back to preoperative values by postoperative day 5 independently on the adopted surgical access. Further studies are needed to elaborate whether these small differences may still be relevant to patient management.
Keywords: lung cancer; VATS; systemic inflammation